Enhancing of Heat Transfer Rate in the Heat Exchanger with Wavy Winglets Experimentally - Adnan Q. Ibrahim; Riyadh S. Alturaihi (Journal of Engineering)
Heat convection plays an important role in many industries, equipment, and human lives, and heat exchangers emerge as fundamental devices for controlling this crucial orientation. The primary objective of this work was to assess the effect of single- and two-phase flows associated with wavy winglets on heat exchanger performance. Two-phase flows as the working fluid with wavy winglets are used in the oval tube bank heat exchanger (HE). The Reynolds number area (3639–4813) is investigated in this experimental work. Wavy winglets at an attack angle of 15° have been shown to affect heat transfer rate through comparisons between the experimental results and various water-air mixture flow rates (Qw = 15, 17.5, and 20 Lpm) (Qa = 8.33, 16.67, and 25 Lpm). A Nusselt number (Nu) is increased by 64.5%, and the friction factor (f) is decreased by 12.6% in water flow; the Nu is increased by 15.5%, and f remains almost constant in water-air mixture flow at moderate turbulent flow. It can be noted that the Nu and the performance parameter (j/f) are directly proportional to the velocity of flow at moderate turbulent flow with any increase in turbulent flow, and the Nu and j/f are inversely proportional to the velocity of flow. Many parameters have been studied experimentally to establish their impact on performance parameters.